Which adult patients with asymptomatic microscopic hematuria require further evaluation to rule out occult malignancy?. Issue 1 (January 2018) - Barroso, Violeta; Nissen, Elise; Shaver, Julia
Abstract : EVIDENCE‐BASED ANSWER : A validated risk index for asymptomatic microscopic hematuria (AMH) that incorporates age, sex, history of gross hematuria, history of smoking, and degree of hematuria (<25 or >25 red blood cells per high‐power field [RBC/HPF]) can identify a low‐risk group of patients with a 0.2% risk of urinary tract malignancy, suggesting that these low‐risk patients may not benefit from further evaluation (SOR: B, prospective cohort study). The American Urological Association (AUA) recommends computed tomography (CT) urography as the imaging test of choice, but also acknowledges that serious causes of AMH in younger patients (<35 years) without risk factors are rare, and so suggests ultrasound with or without intravenous urography as an alternative (SOR: C, expert opinion).